Impact of gneissic layering and localized incipient melting upon melt flow during experimental deformation of migmatites. (April 2016) - Ganzhorn, A.C.; Trap, P.; Arbaret, L.; Champallier, R.; Fauconnier, J.; Labrousse, L.; Prouteau, G.
Abstract: In this study, we test experimentally the role of compositional layering as a key parameter for controlling melt flow in a natural migmatite during coaxial deformation. We performed in – situ pure-shear experiments on two natural gneisses. The first gneiss is weakly foliated with minerals homogenously distributed. The second gneiss shows a pronounced compositional layering of alternating quartz – feldspar – rich and biotite – muscovite – rich layers. Experimental conditions were selected to obtain homogeneous melt distribution in the homogeneous gneiss and heterogeneous melt distribution in the layered gneiss. Initial melt distribution is not modified by deformation in experiments on the homogeneous gneiss, implying that melting products did not migrate from their initiation sites. In contrast, melt flowed in shear zones or in inter-boudin positions during experimental deformation of the heterogeneous gneiss. These experiments attest to the strong influence of initial gneissic layering on melting pattern, melt segregation and flow during deformation of partially molten rocks. Highlights: Purpose: examine experimentally control of anisotropies on melt flow in migmatites. Experiments on a homogeneous gneiss and one with strong mineral layering. Initial anisotropy strongly controls melt flow and segregation at sample-scale. Initial anisotropy also controls deformation distribution and its partitioning. Boudinage occurs in the gneiss with mineral layering.